Preventative oral methylthioadenosine is anti-inflammatory and reduces DSS-induced colitis in mice - Benight, Nancy M. (American Physiological Society, 2012)
Methylthioadenosine (MTA) is a precursor of the methionine salvage pathway and has been shown to have anti-inflammatory properties in various models of acute and chronic inflammation. However, the anti-inflammatory properties of MTA in models of intestinal inflammation are not defined. We hypothesized that orally administered MTA would be bioavailable and reduce morbidity associated with experimental colitis. We examined clinical, histological, and molecular markers of disease in mice provided oral MTA before (preventative) or after (therapy) the induction of colitis with 3% dextran sulfate sodium (DSS). We found a reduction in disease activity, weight loss, myeloperoxidase activity, and histological damage in mice given preventative MTA compared with DSS alone. We also found that equivalent supplementation with methionine could not reproduce the anti-inflammatory effects of MTA, and that MTA had no detectable adverse effects in control or DSS mice. Expression microarray analysis of colonic tissue showed several dominant pathways related to inflammatory cytokines/chemokines and extracellular matrix remodeling were upregulation by DSS and suppressed in MTA-supplemented mice. MTA is rapidly absorbed in the gastrointestinal tract and disseminated throughout the body, based on a time course analysis of an oral bolus of MTA. This effect is transient, with MTA levels falling to near baseline within 90 min in most organs. Moreover, MTA did not lead to increased blood or tissue methionine levels, suggesting that its effects are specific. However, MTA provided limited therapeutic benefit when administered after the onset of colitis. Our results show that oral MTA supplementation is a safe and effective strategy to prevent inflammation and tissue injury associated with DSS colitis in mice. Additional studies in chronic inflammatory models are necessary to determine if MTA is a safe and beneficial option for the maintenance of remission in human inflammatory bowel disease.